Effect of IGF-I and TNF-α on intensification of steroid pathways in women with PCOS phenotypes are not identical. Enhancement of progesterone pathway in women with PCOS increases the concentration of TNF-α. (1st September 2016) - Szczuko, M.; Zapałowska-Chwyć, M.; Drozd, A.; Maciejewska, D.; Starczewski, A.; Stachowska, E.
Abstract: Objective : The aim of this study was to determine the correlations between the concentration of tumor necrosis factor (TNF-α) and insulin-like growth factor I (IGF-I) in each woman with polycystic ovary syndrome (PCOS) phenotypes based on the levels of androgen. Methods : Two groups of women with PCOS differing in their levels of androgens. The test group composed of 39 women with PCOS according to the Rotterdam criteria in their reproductive age. The hormonal levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), thyroid stimulating hormone (TSH), prolactin (PRL), androstenedione, testosterone (T), estradiol (E2 ) and sex hormone binding globulin (SHBG) were measured. Correlations analysis were performed calculating Spearman's rank correlation coefficient of hormones with relation to TNF-α and IGF-I. Results : There was a medium positive correlation of IGF-1 with LH levels ( p < 0.05) and negative medium correlation of TNF-α with of dehydroepiandrosterone (DHEA)-SO4 levels ( p < 0.05) only in group of PCOS women with elevated androgens. Conclusion : Analysis of TNF-α showed that women with high testosterone negative correlation between level of TNF-α and the concentration of DHEA-SO4. Inflammatory state involving TNF-α in women with PCOS and high concentration of androgens is caused by intensified Δ4 (progesterone) pathway and omitted or limited Δ5 (dehydroepiandrosterone) pathway of testosterone biosynthesis.